Megavoltage photon FLASH for preclinical experiments - Taylor, Edward R. J. F.; Tullis, Iain D. C.; Vojnovic, Borivoj; Petersson, Kristoffer (Medical physics (Lancaster), 2025)
Background FLASH radiotherapy using megavoltage (MV) photon beams should enable greater therapeutic efficacy, target deep seated tumors, and provide insights into mechanisms within FLASH. Purpose In this study, we aim to show how to facilitate ultra‐high dose rates (FLASH) with MV photons over a field size of 12–15 mm, using a 6 MeV (nominal) preclinical electron linear accelerator (linac). Our intention is to utilize this setup to deliver FLASH with MV photons in future preclinical experiments. Methods An electron linear accelerator operating at a pulse repetition frequency of 300 Hz, a tungsten target, and a beam hardening filter were used, in conjunction with beam tuning and source‐to‐surface distance (SSD) reduction. Depth dose curves, beam profiles, and average dose rates were determined using EBT‐XD Gafchromic film, and an Advanced Markus ionization chamber was used to measure the photon charge output. Results A 0.55 mm thick tungsten target, in combination with a 6 mm thick copper hardening filter were found to produce photon FLASH dose rates, with minimal electron contamination, delivering dose rates > 40 Gy/s over fields of 12–15 mm. Beam flatness and symmetry were comparable in horizontal and vertical planes. Conclusion Ultra‐high average dose rate beams have been achieved with MV photons for preclinical irradiation fields, enabling future preclinical FLASH radiation experiments.